Bezpieczeństwo – teoretyczny wymiar ponadczasowej wartości - Łebkowska, Joanna (Przegląd Strategiczny, 2011)
Common awareness of threats and dangers, which has become an integral part of nature and mankind, has caused the situation when determination to guarantee safety makes this value timeless. According to H. Kissinger the notion of safety is nowadays ‘the foundation of every human action’. That is why, in literature, one can see a very wide scope of safety categories in its defining. The aim of the article is the attempt to explain the notion and to show the essence of safety. Taking into consideration ambiguity of the notion of safety, attention has been directed to its description as the state. At the same time, safety has been described as a process where the state of safety and its organization are subjects of dynamic transformations proportionally to changes in safety conditions. Importance of geopolitical evolution and the progress of science and technology in the last decade of 20th century for transformation of views concerning creation of contemporary national security has been stressed. Realities of 21st century cause that safety of society depends mainly on global and national security. That is why the synthesis of contemporary description of national security has been presented, taking into consideration social category, functional and structural meaning. The attempt of theoretical presentation of the term of safety leads to fundamental conclusions. Firstly, safety undergoes the laws of social systems movements. Secondly, the phenomenon should be analysed thoroughly, noticing its subjective, objective and spatial diversity.